Incidence and factors associated with SARS-CoV-2 infection and re-infection among people experiencing homelessness in Toronto, Canada: A prospective cohort study - Lucie Richard; Brooke Carter; Michael Liu; Rosane Nisenbaum; Stephen W. Hwang (PLoS ONE, 2025)
People experiencing homelessness are at elevated risk of SARS-CoV-2 infection, yet estimates generally exclude re-infections and rely on data sources affected by testing policies or study timing. In this prospective cohort study, we report incidence of SARS-CoV-2 infection and re-infections over time using a combination of community-based and study-administered testing, and assessed individual and housing-related factors associated with new infection. Individuals experiencing homelessness were randomly selected from 62 sites across Toronto, Canada, between June and September 2021. Participants provided detailed surveys and biological samples to test for SARS-CoV-2 (by RT-PCR and ELISA) every three months for one year. Self-reported data were verified and augmented through linkage to health administrative databases. Among 640 participants who completed 2,401 interviews, we identified 613 SARS-CoV-2 infection events, representing an incidence rate of 35.3 infections/100-person years (95% CI 31.6-39.4) prior to the onset of Omicron and 97.2 infections/100 person-years (95% CI 86.8-108.8) after Omicron. Nearly 30% (n = 182) of these events were re-infections. In multivariable models, post-Omicron interviews (adjusted rate ratio [aRR] 3.54 [95% CI 3.12-4.02]), history of prior COVID-19 infection (1 infection aRR 2.55 [95% CI 2.29-2.83]; 2 + infections aRR 2.28 [95% CI 1.80-2.89]) and residing in high- or moderate-exposure risk (congregate and shared) housing settings (high-exposure aRR 1.74 [95% CI 1.43-2.11]; moderate-exposure aRR 1.39 [1.15-1.68]) were most significantly associated with new infection. Our findings highlight that existing reports significantly underestimate SARS-CoV-2 infection burden among people experiencing homelessness, but confirms previously reported factors associated with infection, including congregate and shared housing settings. Reducing reliance on overcrowded emergency housing is necessary to reduce infection incidence in this population as well as associated inequities in downstream acute and chronic complications.